Immune-mediated Neuropathies in Clinical Practice: A Narrative Review - Rahman, Aminur (Journal of Bangladesh College of Physicians and Surgeons, 2025)
The spectrum of immune-mediated polyneuropathies has expanded with the discovery of chronic, steroid-responsive polyneuropathy 50 years ago, and the identification of acute monophasic paralysis, later named Guillain-Barré syndrome, nearly a century ago. Numerous subtypes of these polyneuropathies are still being identified, such as multifocal motor neuropathy (MMN), chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) and paraproteinemic neuropathies (PN). Most of these illnesses are thought to be brought on by autoimmunity against proteins found at the node of Ranvier or peripheral nerve myelin; however, not all disorders have been linked to disease-associated autoantibodies. The presence of certain anti-glycoconjugate antibodies suggests a molecular mimicking mechanism at work and can help classify these illnesses, albeit this approach often just confirms the clinical diagnosis. Presently, multifocal motor neuropathy with conduction block, another subgroup of treatable motor neuropathies, is characterized by the electrophysiological presence of conduction blocks. The many kinds of immune-mediated neuropathies make it difficult to make the correct diagnosis in day-to-day clinical practice. Immunotherapies, such as plasma exchange, intravenous immunoglobulin, and corticosteroids, are typically used in the therapy of these illnesses. The treatment choices for these debilitating diseases should be expanded by advancements in clinical criteria and the development of further immunotherapies targeted to individual diseases. The aim of this review is to get a glimpse at these different perspectives that may aid these diseases practical approach to diagnosis, management and prognosis. J Bangladesh Coll Phys Surg 2025; 43: 59-76